Parameterization-based trajectory planning for an 8-DOF manipulator with multiple constraints - Ziwu Ren; Zhongyuan Wang; Xiaohan Liu; Rui Lin (Biomimetic Intelligence and Robotics)
A physically feasible, reliable, and safe motion is essential for robot operation. A parameterization-based trajectory planning approach is proposed for an 8-DOF manipulator with multiple constraints. The inverse kinematic solution is obtained through an analytical method, and the trajectory is planned in joint space. As such, the trajectory planning of the 8-DOF manipulator is transformed into a parameterization-based trajectory optimization problem within its physical, obstacle and task constraints, and the optimization variables are significantly reduced. Then teaching–learning-based optimization (TLBO) algorithm is employed to search for the redundant parameters to generate an optimal trajectory. Simulation and physical experiment results demonstrate that this approach can effectively solve the trajectory planning problem of the manipulator. Moreover, the planned trajectory has no theoretical end-effector deviation for the task constraint. This approach can provide a reference for the motion planning of other redundant manipulators.